Pengaruh Promosi Flash Sale dan Electronic Word of Mouth terhadap Perilaku Pembelian Impulsif melalui Mediasi Fear of Missing Out (FOMO) pada Brand Elizabeth di Kalangan Generasi Z - Dian Widyanti; Piji Pakarti; Mahmud Mahmud; Roymon Panjaitan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of flash sale promotions and electronic word of mouth on impulsive buying behavior through the mediation of Fear of Missing Out (FOMO) on Elizabeth Brand among Generation Z in Semarang City. This study uses the Theory of Planned Behavior (TPB) by Ajzen. The research method used is a quantitative approach with data collection through questionnaires to 224 respondents and analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS). The results show that flash sale promotions and electronic word of mouth have a positive and significant effect on FOMO and impulsive buying behavior, and FOMO has a positive and significant effect on impulsive buying behavior, and FOMO plays a role in mediating between flash sale promotions and electronic word of mouth on impulsive buying behavior of Generation Z. Digital marketing strategies based on flash sales and electronic word of mouth need to be managed by paying attention to the psychological aspects of Fear of Missing Out in order to be able to encourage purchasing behavior more effectively in Generation Z.